The Comparison of WLS and DWLS Estimation Methods in SEM to Construct Health Behavior Model - Ferra Yanuar; Fadilla Nisa Uttaqi; Aidinil Zetra; Izzati Rahmi; Dodi Devianto (Science and Technology Indonesia, 2022)
It is unknown how reliable various point estimates, standard errors, and standard several test statistics are for standardized SEM parameters when categorical data used or misspecified models are present. This paper discusses the comparison between WLS and DWLS for examining hypothesized relations among ordinal variables. In SEM, the polychoric correlation is employed either in WLS or DWLS. This study constructs the Health behavior model as an endogenous latent variable in which exogenous latent variables are Perceived susceptibility and Health motivation. All indicators are in categorical types. Thus, data are not multivariate normal, or the model could be misspecified. This study compares the values of standard deviation and coefficient determination to determine a better model. The criteria for the goodness of fit for the overall model are based on RMSEA, CFI, and TLI values. This present study found that the WLS estimator method resulted in better values than DWLS’s.